Comparative Analysis of the Use of Customary Law in Land Dispute Resolution: Case Study Approach - Judijanto, Loso; Utama, Andrew Shandy; Sahib, Abdul; Sumarna, M. Ibnu; Zulfikar, Muh. Reza (Rechtsnormen: Journal of Law, 2024)
Background. Background Customary law is a legal system that has existed since ancient times in many communities in Indonesia. However, with modernization and globalization, the use of customary law in land dispute resolution is often overlooked or defeated by positive law. Therefore, it is important to conduct a comparative analysis of the use of customary law in land dispute resolution to understand its relevance in the context of modern law. Purpose. The purpose of this study is to investigate the comparative use of customary law and positive law in land dispute resolution. The specific objective is to evaluate the effectiveness, fairness and sustainability of each approach in resolving land conflicts. Method. The research method used is a case study approach. Case studies were conducted on several cases of land dispute resolution in various regions in Indonesia involving the use of customary law and positive law.   Results. The results show that the use of customary law in land dispute resolution often provides solutions that are more in line with local needs and traditional values of the community. However, positive law also has an important role in providing legal certainty and protection of individual rights. Conclusion. Based on the results of the comparative analysis, it is concluded that both approaches have their own advantages and disadvantages. Therefore, the integration between customary law and positive law can be a more optimal solution in resolving land disputes in Indonesia, by taking into account the local context and individual rights in a balanced manner.